Strategi Meningkatkan Kemampuan Berbahasa dengan Percaya Diri untuk Mahasiswa Pendidikan Teknik Elektro di Universitas Negeri Medan - Andre Jonatan; Hineru Sidabutar; Intan Panggabean; Imanuel Simarmata; Lilis Manik; Sahatma Sinaga; Wirna Manullang (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to identify and develop effective strategies to enhance language skills with self-confidence among students of Electrical Engineering Education at Universitas Negeri Medan. Language proficiency and self-confidence are crucial factors in supporting both academic and professional communication in the field of electrical engineering, especially when students are required to present ideas, convey research findings, and interact in the workplace. The research employed a qualitative method with direct observation, in-depth interviews, and literature study to obtain valid and comprehensive data. The findings indicate that the implementation of interactive learning methods, regular speaking practice, the utilization of technological media, and the reinforcement of a positive mindset significantly improve students’ language abilities while simultaneously fostering their confidence in communication. Furthermore, the presence of a supportive learning environment and the active role of lecturers as facilitators contribute to encouraging students to perform confidently in public. The implications of this study are expected to serve as a reference for educators and educational institutions in improving the quality of language learning, particularly in technical study programs. Thus, graduates are not only equipped with technical expertise but also possess strong communication competencies to face global challenges.